2007
DOI: 10.1002/ejoc.200700606
|View full text |Cite
|
Sign up to set email alerts
|

Domino Transformations of gem‐Trifluoroacetyl(bromo)alkenes under the Action of Secondary Amines

Abstract: Keywords: Enones / Nucleophilic substitution / Domino reactions 2-Bromo-3-arylpropenyl trifluoromethyl ketones underwent aza-Michael/hydroxyalkylation domino reactions triggered by secondary amines to give unexpectedly 2-amino-1-trifluoromethyl indenols in good yields. The process was found to involve the intermediate formation of captodative aminoalkenes. Treatment of 2-bromo-3-thienyl derivatives with the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Trifluoromethylated α‐bromoenones 1 ( Z ‐isomer only) are readily accessible from the corresponding enones through a bromination/dehydrobromination sequence . We started our investigation by the screening of reaction parameters for the addition of phenylmagnesium bromide to α‐bromoenone 1a .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trifluoromethylated α‐bromoenones 1 ( Z ‐isomer only) are readily accessible from the corresponding enones through a bromination/dehydrobromination sequence . We started our investigation by the screening of reaction parameters for the addition of phenylmagnesium bromide to α‐bromoenone 1a .…”
Section: Resultsmentioning
confidence: 99%
“…The conjugate nucleophilic addition to functionalized enones is a straightforward method for the carbon–carbon or carbon–heteroatom bond formation. In this context, we recently demonstrated that trifluoromethylated α‐bromoenones are excellent Michael acceptors and valuable starting materials in the reaction with nitrogen‐bearing mono‐ or binucleophiles for assembly of a diversity of trifluoromethylated linear as well as carbo‐ and heterocyclic derivatives . These enones are ambivalent bielectrophiles bearing electrophilic centers at the carbonyl function and at the olefinic β‐carbon; therefore, they can react with nucleophiles either in 1,2‐ or 1,4‐addition mode.…”
Section: Introductionmentioning
confidence: 99%
“…Polyfunctionality and accessibility of haloalkenyl trifluoromethyl ketones makes them undoubtedly advantageous as intermediate products for the preparation of various biologically active substances and analogs of natural compounds. For example, we recently reported on unexpected one-pot transformation of 4-aryl-3-bromo-1,1,1-trifluoromethylbut-3-en-2-ones into indenols by the action of secondary amines [7,8].With a view to understand specific reactivity of alkenyl trifluoromethyl ketones having a halogen atom in the α-position, it is necessary to thoroughly analyze their structure and the nature of electronic interactions in their molecules. In the present work we examined the stereoelectronic structure of α-haloalkenyl trifluoromethyl ketones in comparison with their nonfluorinated analogs on the basis of the results of DFT quantum-chemical calculations (B3LYP/6-311G**) and IR spectral data.…”
mentioning
confidence: 99%
“…Polyfunctionality and accessibility of haloalkenyl trifluoromethyl ketones makes them undoubtedly advantageous as intermediate products for the preparation of various biologically active substances and analogs of natural compounds. For example, we recently reported on unexpected one-pot transformation of 4-aryl-3-bromo-1,1,1-trifluoromethylbut-3-en-2-ones into indenols by the action of secondary amines [7,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation